Health chain-block chain based electronic healthcare record system with access and permission management - Bhawna Saraswat; Ashwini Kumar; Sakshi Sharma; Kul Bhushan Anand (Measurement: Sensors, 2023)
An electronic health record (EHR) is a technology that allows you to keep track of your health information. It keeps computerized records of several healthcare organizations. Records are exchanged via enterprise-wide data systems as well as other networking technologies and exchanges. Patients nowadays expect immediate access to their health information. However, the health sector comes with immediate access to data, and there are worries about the privacy and security of medical records of patients. As a result, a blockchain-based solution can assist in resolving this issue. The blockchain has the potential to beat the conventional centralized system, which suffers from a severe lack of accessibility. The current healthcare system is often seen as being both costly and convoluted. However, with improved health data management and insurance providers, this may be reduced via the use of Blockchain Technology (BT). It is the goal of the developers of BT to make it possible to keep track of financial transactions without having to rely on a central authority or a bank. Innovations in BT have allowed for better health records, insurance billing, and smart contract transactions, and it also enable a decentralized data structure of activities, as well as eternal availability and security over health information. Access to medical records, instrument tracking, prescription databases, hospital facilities, and property lifetime all inside a blockchain architecture is made possible by BT that also greatly improves the seamless integration of health information. The use of BT in the medical field has this advantage as one of its primary advantages. Access to a patient's medical history is crucial for prescribing the right treatment, and BT has the potential to greatly enhance the current state of public healthcare delivery. This paper offers a block chain-based scheme called “Health Chain” as a solution for maintaining medical records. Health Chain is made to be better than the existing systems since it gives patients, health professionals, and other external stakeholders safe, efficient, and ubiquitous medical information available while maintaining the patients' confidentiality. To regulate operations and restrict access to digital health records, Health Chain uses timed-based smart contracts. In addition, it uses cutting-edge encryption methods to boost security. This study suggests a new reward system that uses healthcare professionals to track patients' medical information and construct additional units. Numerous tests are run to assess the proposed Health Chain model's performance, and the findings demonstrate that the proposed suggestion effectively manages a huge dataset called (nCOV19) from the Covid-19 study with little delay. Maximum efficiency will be expected to be attained by 98%, transaction latency by 95%, overall system execution time by 96%, data security by 92%, and data scalability by 95%, according to the suggested research.